Metode Istinbat Al-Hukm Melalui Pendekatan Kebahasaan - Darmawan, Darmawan (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The Al-Qur'an and Hadith are the primary sources of Islamic law. Still, the interpretation of the Al-Qur'an and Hadith gives rise to various understandings that have multiple interpretations, so there is a need for a more precise scope as an approach in istinbat al-hukm of Al-Qur'an. Qur'an and Hadith. The linguistic approach is one of the legal instruments and methodologies from the two sources above in terms of sentence structure and semantics (meaning content). In the context of Istinbat al-hukm through a linguistic approach, it can be seen and reviewed by the editorial or lafaz Arabic language that five main aspects are worth paying attention to, namely: (1) the form of Amr (command) and nahy (prohibition); (2) the clarity side of the meaning; (3) the scope of the meaning; (4) the side shows the meaning; and (5) the use or application side. The results of this study emphasize methodological studies as a path and approach in Istinbat al-hukm from the main references, namely from the Al-Qur'an and Hadith.